Performance appraisal and feedback - Hutchinson, Sue (Henry Stewart Talks, 2020)
What is a performance appraisal?, What 360-degree appraisal can do for your business, Types of performance appraisal, Dangers of ratings, The impact of giving feedback, Performance appraisal conversations